Community Structure of Macroalgae in Kotok Besar Island, Kepulauan Seribu Jakarta - Gabrilla, Gabrilla; Handayani, Sri; Jalip, Ikna Suyatna (Proceeding International Conference on Global Resource Conservation, 2013)
Kotok Besar Island is one of the islands that are included in the utilization zone from a Kepulauan Seribu National Park Authority. This island has area of 30 ha which still has the potential diversity of macroalgae based on studies that have been done before. This research aims to determine the condition and diversity of macroalgae. Research in Kotok Besar Island, Kepulauan Seribu DKI Jakarta was conducted in February â August 2012 using plot size of 1Â  x 1 m which combined with line transect method. The result of this research showed that there are 3 divisions macroalgae (Chlorophyta, Phaeophyta and Rhodophyta) and 30 species, there are 16 species Chlorophyta, 8 species Phaeophyta and 6 species Rhodophyta. Macroalgae diversity divided into four research stations, including middle category of 2.161 - 2.647. Congruence index of macroalgae in Kotok Besar Island for each station has a different study. A comparison of highest similarity index types are found in the south west of the station is 88,37 %, while the lowest ratio found in the east to the train station south is 73,13%.Â Keywords: Community, Kotok Besar Island, Macroalgae, StructureÂ